The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3389/feart.2020.585733
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Level Gas Monitoring: A New Approach in Earthquake Research

Abstract: Fluid anomalies were often considered as possible precursors before earthquakes. However, fluid properties at the surface can change for a variety of reasons, including environmental changes near the surface, the response of the superficial fluid system to loads associated with the mechanical nucleation of earthquake fractures, or as a result of transients in fluid flow from the depths. A key problem is to understand the origin of the anomaly and to distinguish between different causes. We present a new approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…This indicates a hydraulic connection between the boreholes. This hypothesis was also supported by Woith et al (2020), who documented a decrease in the gas flow and bubble fraction (Figure 4D) on the 30th of August. At the same time, the Rn concentration of the F3 drill mud reached its maximum.…”
Section: Relation Between Fluid Parameters and Cosupporting
confidence: 74%
See 2 more Smart Citations
“…This indicates a hydraulic connection between the boreholes. This hypothesis was also supported by Woith et al (2020), who documented a decrease in the gas flow and bubble fraction (Figure 4D) on the 30th of August. At the same time, the Rn concentration of the F3 drill mud reached its maximum.…”
Section: Relation Between Fluid Parameters and Cosupporting
confidence: 74%
“…This observation was further studied by Nickschick et al (2015), who hypothesized the existence of pull-apart basin-like structures inside the PPZ, and it was tested by Kämpf et al (2019), who instead identified en-echelon faults, which act as fluid channels to depth. Barometric pressures (note inverted scale in Figure 4E) are negatively correlated to the gas flow and bubble fraction at F1 (Woith et al, 2020). Fischer et al (2020) explained this by proposing that elevated barometric pressures contribute to the dissolution of CO 2 that in turn hampers degassing.…”
Section: Relation Between Fluid Parameters and Comentioning
confidence: 97%
See 1 more Smart Citation
“…1). In particular, two existing monitoring wells, F1 and F2 (Bussert et al, 2017;Fischer et al, 2020), were complemented by the F3 drill hole; these three adjacent boreholes, F1 (30 m), F2 (70 m) and F3 (230 m), provide continuous monitoring of fluids at high sampling rates to acquire fluid parameters (gas flow, water temperature and water level/pressure) as well as chemical (CO 2 , Ar, N 2 , O 2 , He, H 2 and CH 4 ) and isotopic (δ 13 C CO 2 , δ 18 O CO 2 and 222 Rn) gas content (Woith et al, 2020). Additionally, samples for laboratory analysis of He, Ne and Ar isotopes are taken repeatedly (roughly every 2 months), as theses isotopes are useful tracers for constraining the fluid origins and mixing ratios of mantle components.…”
Section: Description Of Drillings Monitoring and Scientific Conceptsmentioning
confidence: 99%
“…Ultimately, a borehole seismometer will be installed at the bottom of F3 and will be complemented by a capillary tube to collect "fresh" gases from the CO 2 horizon at depth, directly at the point where the fluids enter the borehole to avoid possible contamination or impact from external processes. Further details on the instrumentation of this mofette field with massive CO 2 degassing (up to 97 t d −1 ) as well as the first monitoring results are summarized in Fischer et al (2020), Woith et al (2020) and Daskalopoulou et al (2021). Once the novel monitoring system is fully operational, fluid transients will be able to be observed in great detail.…”
Section: Fluid and Seismic Monitoring And Microbiological Research -C...mentioning
confidence: 99%